Wanita dalam Chanoyu pada Novel “The Life of an Amarous Man” Karya Ihara Saikaku (Kajian Sastra dan Budaya Jepang ) - Alo Karyati (Chi'e: Journal of Japanese Learning and Teaching, 2022)
This study examines the role of women in chanoyu or the Japanese tea ceremony contained in the novel "The Life An Amarous Man" by Ihara Saikaku. This novel tells how the role of women (maids) in entertaining guests, making tea and attracting guests to come to the "tea house" or tea house. Chanoyu, in this novel, takes place in a tea house where the servants are a woman (maid). Chanoyu is one of the Japanese tea drinking cultures that is still preserved. Japan is rich in various traditional cultures still practised today, one of which is the chanoyu culture. Chanoyu is a literary activity in culture. So that chanoyu is very closely related to literature because, in the Chanoyu process, there are noble values, such as Japanese ritual activities, which are very sacred and have stages as elements in the Japanese teachings of patience and tenacity well as never giving up. These noble values ​​are part of literature. The formulation of the problem in this study relates to the role of women as maids in the tea house, and the position of the tea house is identical to chanoyu.